The Influence of Audit Tenure, Audit Delay, Audit Fee, Audit Rotation and Auditor Specialization on Audit Quality - Ratnasari, Ratih; Afrizal, Afrizal; Mansur, Fitrini (Jurnal Cakrawala Akuntansi, 2025)
The purpose of this study is to obtain empirical evidence regarding the influence of audit tenure, audit delay, audit fees, auditor rotation, and auditor specialization on audit quality. The study was conducted on transportation and logistics companies listed on the Indonesia Stock Exchange from 2019 to 2023. The sample was selected using purposive sampling, resulting in 20 companies with a total of 100 observational data points. Audit quality was measured using audit opinion as a proxy, employing a dummy variable where 1 indicates an unqualified opinion (WTP), and 0 indicates other types of audit opinions. Logistic regression analysis was used in this study, with the help of SPSS version 27. The results showed that auditor specialization has a significant influence on audit quality, while other variables namely audit tenure, audit delay, audit fees, and auditor rotation do not have a significant impact on audit quality.